Hubungan Perkembangan Politik Hukum dengan Tindak Pidana Korupsidi Indonesia - Arifah Putri Nabilah; Neta Kania Salsabila; Praba Caesar Bagaskara; Aryo Nugroho; Amelia Miska Rahayu (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
The problem of corruption in Indonesia is currently a chronic problem. In Indonesia, criminal acts of corruption areregulated in Law Number 31 of 1999 concerning Eradication of Corruption Crimes. The problem of corruption ispart of the problem of legal politics. Legal politics itself can simply be formulated as legal expertise (Legal Policy)that will be or has been implemented nationally by the government, including the understanding of how politicsinfluences law by looking at the configuration of the forces behind and law enforcement. The purpose of conductingthis research is to provide an overview of the role of legal politics in eradicating corruption in Indonesia. The methodused in this research is descriptive analysis method, namely by collecting data in accordance with the actual datathen compiled, processed and analyzed to be able to provide an overview of the existing problems